(untitled) (Research, Society and Development, 2019)
The representation of cultural issues in the open educational resources (OER) is very important, because in addition to meeting the premises of the REAs, favoring reuse and content quality, it contributes to a more open and inclusive education by representing the cultural contexts of students and teachers in REAs. The purpose of this research is to present a case study on the design of multicultural open educational resources (REAM) using a support model to represent cultural issues during the design process. For this research a qualitative-quantitative approach was used, having as strategy a case study in the accomplishment of a design experiment in workshop format with 18 students and 1 professor of the Federal Institute of Education, Science and Technology of Mato Grosso - Campus São Vicente, in which educational videos were produced, using REAM Metamodel as support. Data analysis showed that workshop participants understood the need to represent cultural issues in educational resources and recognized the utility and relevance of REAM Metamodel in the design of REAMs.